Celastrol Inhibited Human Esophageal Cancer by Activating DR5-Dependent Extrinsic and Noxa/Bim-Dependent Intrinsic Apoptosis - Chen, Xihui; Wang, Shiwen; Zhang, Li; Yuan, Shuying; Xu, Tong; Zhu, Feng; Zhang, Yanmei; Jia, Lijun (Frontiers in Pharmacology, 2022)
Esophageal squamous cell carcinoma (ESCC) is one of the deadliest digestive system cancers worldwide lacking effective therapeutic strategies. Recently, it has been found that the natural product celastrol plays an anti-cancer role in several human cancers by inducing cell cycle arrest and apoptosis. However, it remains elusive whether and how celastrol suppresses tumor growth of ESCC. In the present study, for the first time, we demonstrated that celastrol triggered both extrinsic and intrinsic apoptosis pathways to diminish the tumor growth of ESCC in vivo and in vitro. Mechanistic studies revealed that celastrol coordinatively induced DR5-dependent extrinsic apoptosis and Noxa-dependent intrinsic apoptosis through transcriptional activation of ATF4 in ESCC cells. Furthermore, we found that FoxO3a-Bim pathway was involved in the intrinsic apoptosis of ESCC cells induced by celastrol. Our study elucidated the tumor-suppressive effects of celastrol on ESCC and revealed a previously unknown mechanism underlying celastrol-induced apoptosis, highlighting celastrol as a promising apoptosis-inducing therapeutic strategy for ESCC.